2018
DOI: 10.7554/elife.32637
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin underlies the evolution of sleep loss in the Mexican cavefish

Abstract: The duration of sleep varies dramatically between species, yet little is known about the genetic basis or evolutionary factors driving this variation in behavior. The Mexican cavefish, Astyanax mexicanus, exists as surface populations that inhabit rivers, and multiple cave populations with convergent evolution on sleep loss. The number of Hypocretin/Orexin (HCRT)-positive hypothalamic neurons is increased significantly in cavefish, and HCRT is upregulated at both the transcript and protein levels. Pharmacologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 77 publications
1
45
0
1
Order By: Relevance
“…Studies in zebrafish have identified a central wake-promoting role for the catecholamines dopamine and norepinephrine, and hypothalamic neurons expressing HCRT that consolidate wakefulness ( 30 , 31 ). We previously reported that functional differences in β-adrenergic and HCRT signaling contribute to sleep loss in Pachón cavefish ( 32 , 33 ), but the role of these signaling pathways in sleep regulation and the neuroanatomy of catecholamine and HCRT neurons have not been characterized in other populations of cavefish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in zebrafish have identified a central wake-promoting role for the catecholamines dopamine and norepinephrine, and hypothalamic neurons expressing HCRT that consolidate wakefulness ( 30 , 31 ). We previously reported that functional differences in β-adrenergic and HCRT signaling contribute to sleep loss in Pachón cavefish ( 32 , 33 ), but the role of these signaling pathways in sleep regulation and the neuroanatomy of catecholamine and HCRT neurons have not been characterized in other populations of cavefish.…”
Section: Resultsmentioning
confidence: 99%
“…To compare brain activity in sleeping surface fish and cavefish, we pharmacologically induced sleep in all populations of cavefish. Previously, we showed that moderate concentrations of the β-adrenergic antagonist propranolol and HCRT receptor inhibitor N-ethyl-2-[(6-methoxy-pyridin-3-yl)-(toluene-2-sulphonyl)-amino]-N-pyridin-3-ylmethyl-acetamide (EMPA) restore sleep to Pachón cavefish without affecting sleep in surface fish, suggesting enhanced sensitivity to inhibitors of β-adrenergic and HCRT signaling ( 32 , 33 ). Both target receptors have been implicated in human sleep, suggesting the effects of these drugs may be conserved from fish to mammals ( 48 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the wake-promoting neuropeptide Hypocretin/Orexin is up-regulated in cavefish, and ablation of the lateral line reduced Hypocretin to surface fish levels. These findings suggest that evolved differences in sensory systems contribute to sleep loss by modulating hypothalamic function (Jaggard et al, 2018). The identification of sensory and centralbrain mechanisms contributing to sleep loss demonstrate the integral relationship between adaptive changes in sensory processing and sleep regulation.…”
Section: Evolution Of Sleep Loss and Circadian Disruption In Cave Animentioning
confidence: 86%
“…Hcrt is expressed 3-fold more in cave vs. surface fish, and these fish sleep much less than their surface-dwelling counterparts. Indeed, manipulations that promote sleep inhibit Hcrt expression in cave, but not closely related surface fish ( 20 ). Hcrts are also expressed in the avian brain, where they are localized to a single population of neurons spanning the paraventricular and lateral hypothalamus ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%